Application of Lactose Co-Processed Excipients as an Alternative for Bridging Pharmaceutical Unit Operations: Manufacturing an Omeprazole Tablet Prototype via Direct Compression - Raymar Andreina Lara Garcia; Jesús Alberto Afonso Urich; Andreina Isabel Afonso Urich; Dalibor Jeremic; Johannes Khinast (Scientia Pharmaceutica)
Improving the manufacturability of drug formulations via direct compression has been of great interest for the pharmaceutical industry. Selecting excipients plays a vital role in obtaining a high-quality product without the wet granulation processing step. In particular, for diluents which are usually present in a larger amount in a formulation, choosing the correct one is of utmost importance in the production of tablets via any method. In this work, we assessed the possibility of manufacturing a small-molecule drug product, omeprazole, which has been historically manufactured via a multi-step processes such as wet granulation and multiple-unit pellet system (MUPS). For this purpose, four prototypes were developed using several diluents: a co-processed excipient (Microcelac®), two granulated forms of alpha-lactose monohydrate (Tablettose® 70 and Tabletose® 100), and a preparation of microcrystalline cellulose (Avicel® PH102) and lactose (DuraLac® H), both of which are common excipients without any enhancement. The tablets were produced using a single punch tablet press and thoroughly characterized physically and chemically in order to assess their functionality and adherence to drug product specifications. The direct compression process was used for the manufacturing of all proposed formulations, and the prototype formulated using Microcelac® showed the best results and performance during the compression process. In addition, it remained stable over twelve months under 25 °C/60% RH conditions.